2006
DOI: 10.4049/jimmunol.177.10.6833
|View full text |Cite
|
Sign up to set email alerts
|

TIRC7 Inhibits T Cell Proliferation by Modulation of CTLA-4 Expression

Abstract: Ab targeting of TIRC7 has been shown previously to inhibit T cell proliferation and Th1 lymphocyte-associated cytokine production. In this study, we demonstrate that Ab targeting of TIRC7 induces early cell surface expression of CTLA-4. The majority of stimulated CD4+ and CD8+ human T cells coexpress CTLA-4 and TIRC7. Similar to CTLA-4, TIRC7 rapidly accumulates at the site of Ag adhesion upon T cell activation. TIRC7 seems to colocalize with CTLA-4 in human T cells, and both molecules are associated with clat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 45 publications
1
26
1
Order By: Relevance
“…Consistently, TIRC7 À/À T cells exhibited increased proliferation and expression of IL-2, interferon g (IFN-g) and IL-4 [68,69]. Co-localisation of TIRC7 and CTLA-4 occurred close to the site of TCR engagement, but no direct interaction of TIRC7 and CTLA-4 was shown [70]. Therefore, the activation-induced transmembrane protein TIRC7 might be involved in CTLA-4 expression via a yet unknown mechanism.…”
Section: Other Factorsmentioning
confidence: 85%
“…Consistently, TIRC7 À/À T cells exhibited increased proliferation and expression of IL-2, interferon g (IFN-g) and IL-4 [68,69]. Co-localisation of TIRC7 and CTLA-4 occurred close to the site of TCR engagement, but no direct interaction of TIRC7 and CTLA-4 was shown [70]. Therefore, the activation-induced transmembrane protein TIRC7 might be involved in CTLA-4 expression via a yet unknown mechanism.…”
Section: Other Factorsmentioning
confidence: 85%
“…The FoxP3 molecule is a transcription factor that controls the expression of genes responsible for the regulatory phenotype of CD25 [46] -also known as TIRC7 -which is crucially involved in the expression and intracellular trafficking of CTLA-4 to the T cell surface [47,48].…”
Section: Cd25mentioning
confidence: 99%
“…It has been shown to be essential in T cell activation [9,10]. Further studies demonstrated that the antibody against TIRC7 could significantly inhibit the expression of interleukin (IL)-2 and interferon (IFN)-c, without affecting the expression of IL-4, indicating the critical role of TIRC7 in T helper (Th) 1 cells [11].…”
Section: Introductionmentioning
confidence: 98%
“…T cells could provide the suppressive activity in the intestinal inflammation and represent IL-10-secreting Tregs. In addition, TIRC7 was reported to inhibit T cell proliferation by modulation of CTLA-4 expression [10]. Meanwhile, some studies have also documented the importance of TIRC7 on some autoimmune diseases [16]; nevertheless, there were few relevant reports of TIRC7 in hematological diseases.…”
Section: Introductionmentioning
confidence: 98%